Primary Prevention Implantable Cardiac Defibrillators: A Townsville District Perspective - Engstrom, Nathan; Dobson, Geoffrey P.; Ng, Kevin; Letson, Hayley L. (Frontiers in Cardiovascular Medicine, 2020)
Background: Despite major advances in treating patients with severe heart failure, deciding who should receive an implantable cardiac defibrillator (ICD) remains challenging. Objective: To study the risk factors and mortality in patients after receiving an ICD (Jan 2008-Dec 2015) in a regional hospital in Australia. Methods: Eighty-two primary prevention patients received an ICD for ischemic cardiomyopathy (ICM, n=41) and non-ischemic cardiomyopathy (NICM, n=40) with 4.8-yrs follow-up. One patient had mixed ICM/NICM indications. Ventricular arrhythmias were assessed using intracardiac electrograms. Statistical analysis compared the total population and ICM and NICM groups using Kaplan-Meier for survival, Cox regression for mortality predictors, and binary logistic regression for predictors of ventricular arrhythmias (p<0.05). Results: Major risk factors were hypercholesterolemia (70.7%), hypertension (47.6%), and obesity (41.5%). Severe obstructive sleep apnea (OSA) was found exclusively in NICM patients (23.7%, p=0.001). Mortality was 30.5% after 4.8-yrs. The majority of patients (n=67) had no sustained ventricular arrhythmias yet 28% received therapy (n=23), 18.51% were appropriate (n=15) and 13.9% inappropriate (n=11). Patients receiving 2 incidences of inappropriate shocks were 18-times more likely to die (p=0.013). Three sudden cardiac deaths (SCD) (3.7%) were prevented by the ICD. Conclusion: Patients implanted with an ICD in Townsville had 30.5% all-cause mortality after 4.8-yrs. Only 28% of patients received ICD therapy and 13.9% were inappropriate. OSA may have contributed to the fourfold increase in inappropriate therapy in NICM patients. Our study raises important efficacy, ethical and healthcare cost questions about who should receive an ICD, and possible regional and urban centre disparities.